Biomethane to Local Gas Grids - Sirichai Koonaphapdeelert (2020)
© 2020, Springer Nature Singapore Pte Ltd. Biomethane, that satisfies national grid standards, can be injected into national natural gas pipelines. This is the easiest procedure for handling excess biomethane. The biomethane gets mixed with the natural gas and is used wherever the pipeline delivers, for example, power plants, industries, or homes. The quality of the biomethane necessary for injection depends on the country. It is set on a country-by-country basis. In cases where a natural gas pipeline is not locally available, a small-scale biomethane gas grid can be constructed to deliver gas to the local neighborhood and industries. This chapter deals with the design, construction, and operation of a local biomethane gas grid.